Neonatal Sepsis And Antibiotic Sensitivity Patterns At A South African Tertiary Nursery – Evolution Over A 15 Year Period - Naidoo, Nayestha (Department of Paediatrics and Child Health, 2020)
Background Neonatal infection is an important cause of morbidity and mortality in babies. The causative pathogens and their antibiotic susceptibility patterns should be monitored so that treatment regimens can be adjusted to maintain efficacy and avoid selection of resistant organisms. Objectives To compare the incidence of culture positive neonatal sepsis; and to describe the pathogens and antibiotic resistance profiles for significant organsims over a 15-year period in a tertiary nursery in Cape Town. Methods Retrospective blood culture data for 12 months were collected at three time points over a 15-year period. Blood cultures from 2004, 2013 and 2017 were analysed. All neonates with growth on blood cultures were included. Results During 2004 a total of 817 (43.3% of total admissions) blood cultures were taken, 171 (9.1% of total admissions) were culture positive. The most common invasive organisms were Klebsiella pneumoniae (31.8% of invasive organisms), S.aureus (26.1%) and enterococcus species (7.3%). There were 102 contaminants (12.5% of total cultures) of which 7.8% were due to Coagulase-negative Staphylococcus (CONS). In 2013 a total of 1070 (46.8% of total admissions) blood cultures were taken, 124 (5.4% of total admissions) were culture positive. Common invasive organisms were Klebsiella pneumoniae (53.8% of invasive organisms), E. coli (12.8%) and S. aureus (10.3% ). Forty-six blood cultures were deemed contaminated (4.3% of all cultures) and of these 2.1% were due to CONS. In 2017, there were 581 blood cultures taken (26.5% of total admissions), 56 were culture positive (2.6% of total admissions). Commonly occuring invasive organisms were Klebsiella pneumoniae (32.4% of invasive organisms), Group B streptococcus (16.2%) and Acinetobacter (13.5%). Twenty-nine blood cultures were considered contaminated (5.6% of cultures) of which 1.7% were CONS. The gram-negative organisms showed an increasing resistance to penicillin, ampicillin and aminoglycosides but remained sensitive to carbapenems. Conclusions The initial reduction in positive blood cultures from 2004 to 2013 was primarily due to the reduction of contaminants, probably reflecting improved blood sampling techniques. The large reduction in Gram-negative organisms from 2013 to 2017 suggests improved infection control measures , but gram-negative organisms remained prominent in all three cohorts. Emergence of resistant organisms is concerning and in keeping with other nurseries worldwide. These data illustrate the need for antibiotic stewardship, infection control measures and ongoing surveillance.